Pengaruh Kualitas Produk, Word of Mouth dan Kepercayaan terhadap Keputusan Pembelian : Survei pada Konsumen Wardah Cosmetic di Muara Cosmetic & Parfume - Feby Febriandini; Depy Muhamad Pauzy; Barin Barlian (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This research was conducted with the aim of knowing the effect of Product Quality, Word Of Mouth, and Trust on the Purchase Decision of Wardah Cosmetics products. The method used in this study is a survey method using data obtained directly through questionnaires distributed to 100 respondents who are consumers of Wardah Cosmetics. The technique used in this research is multiple linear regression analysis. Based on the results of the study, it can be seen that product quality, word of mouth, and trust simultaneously have a significant effect on purchasing decisions, product quality partially has a significant effect on purchasing decisions, word of mouth partially has a significant effect on purchasing decisions, and trust partially has an effect significant to the Purchase Decision of Wardah Cosmetics products.